BARRIERS TO THE DEVELOPMENT OF UNIVERSITY-BASED SPECIAL PURPOSE VEHICLES - Szarek, Malwina (Management and Administration Journal, 2024)
The aim of this article is to identify the barriers to the development of university-based special purpose vehicles (SPVs) in Poland and to identify the recommendations to address these barriers. As a consequence of the research objective formulated in this way, it was decided to use a literature review, analysis of secondary documents, and a case study method. As part of the case study, in-depth interviews were conducted with the SPV manager and its stakeholders. The literature review concerned the constrictions in the development of the cooperation between science and business on the part of both entrepreneurs and scientists, which consequently translates into barriers in the development of units created to commercialise the results of scientific research created in universities and research institutes, including SPVs. On the basis of the collected research material, barriers to SPV development were defined and then grouped according to the type of constraints (systemic, economic, competence, awareness-cultural) and according to the environment they directly affect (SPVs, scientists, entrepreneurs). In response to the barriers to SPVs development, actions have been proposed to overcome them. The originality of the article stems from the development of the issue of the functioning of SPVs, whose role and capabilities are little understood in both academic and business circles.